Microbiome and the immune system: From a healthy steady-state to allergy associated disruption. (December 2018) - Mezouar, Soraya; Chantran, Yannick; Michel, Justin; Fabre, Alexandre; Dubus, Jean-Christophe; Leone, Marc; Sereme, Youssouf; Mège, Jean-Louis; Ranque, Stéphane; Desnues, Benoît; Chanez, Pascal; Vitte, Joana
Abstract: Microbiome and the immune system are constantly shaping each other, in a mutual aim to thrive, defining the unstable equilibrium of the healthy individual. Microbiome is growingly involved in dysimmune conditions such as allergy, asthma, autoimmunity, and primary or acquired immune deficiencies. The current epidemics of allergic diseases and asthma has long been linked to the microbial environment through the hygiene hypothesis. Progress in the understanding of the microbiome-immune system crosstalk has unraveled a tight connection between microbial communities and the development of allergic diseases and asthma. Disruption of the microbiome affects the immune response of the host and paves the way for disease pathogenesis. Conversely, disease and therapeutic interventions affect microbial communities. We aimed at providing the reader with a view of the state-of-the art of microbiome – immune system crosstalk, with special focus on the loopholes giving potential grip to the pathogenesis of microbiome-related dysimmunity.